Nutrient suppression in passion fruit species: an approach to leaf development and morphology (Colloquium Agrariae. ISSN: 1809-8215, 2021)
The production of passion fruit in commercial areas requires a good correction of nutrients in the soil, however, with nutritional restrictions it can cause symptoms of deficiency expressed mainly in the leaves and stems, which may appear spots, reduced growth, changes in the architecture of these organs mainly in the its size and shape. This work aimed to know the effects caused by the suppression of nutrients in passion fruit species with an approach on their development and leaf morphology. The experimental design was completely randomized (DIC) in a 2x6 factorial scheme where the first factor was composed of two passion fruit species: P. gibertii and P. edulis, interacting with the availability of nutrients, that is, a control group with the supply of all nutrients, with nitrogen suppression (N); phosphorus (P); potassium (K); magnesium (Mg) and iron (Fe), totaling 12 treatments with four replications totaling 48 plots or plastic vessels per experiment. The species P. edulis showed better responses to the variables of development and leaf morphology. The species P. gibertii is more susceptible to nutrient deficiency and showed changes in the color and shape of its leaves with the restriction of nutrients. The nutrients Fe and Mg caused greater restrictions on the development and leaf morphology of passion fruit species. It is necessary to carry out a new study with the species P. gibertii regarding the appropriate concentrations of N, P and K provided in planting and cover, as this species is used as a rootstock in commercial areas.